Diffusion of Interstitial Solutes in Nb-46wt% Ti Alloys Measured by Mechanical Spectroscopy - Grandini, Carlos Roberto [UNESP]; Florencio, Odila; Botta Filho, Walter Jose (Trans Tech Publications Ltd, 2012)
The mechanical properties of metals with a body-centered cubic (bcc) structure, such as Nb, Ta, V, and their alloys, are modified with the introduction of interstitial impurities, such as O, N, C, or H. These metals can dissolve great amounts of O and N, for example, to form solid solutions. The interstitial solute atoms (ISA) in metals with a bcc structure occupy octahedral sites and cause local distortion with tetragonal symmetry. So ISA in these metals forms an elastic dipole that can align along one of the three cubic axis of the crystal. In the present paper, the torsion pendulum technique was employed for the investigation of various interactions among the metallic matrix and different interstitial solutes in the Nb-46wt%Ti alloy. From the relaxation spectra, we obtained the diffusion coefficients, pre-exponential factors, and activation energies for nitrogen in the Nb-46wt%Ti alloy.
Keywords: Nb-Ti alloys; diffusion; interstitials; mechanical spectroscopy